Electrochemical-induced hydroxylation of aryl halides in the presence of Et3N in water. Issue 29 (8th July 2021) - Yang, Li; Zhuang, Qinglong; Wu, Mei; Long, Hua; Lin, Chen; Lin, Mei; Ke, Fang
Abstract : A thorough study of mild and environmentally friendly electrochemical-induced hydroxylation of aryl halides without a catalyst is presented. Abstract : A thorough study of mild and environmentally friendly electrochemical-induced hydroxylation of aryl halides without a catalyst is presented. The best protocol consists of hydroxylation of different aryl iodides and aryl bromides by water solution in the presence of Et3 N under air, affording the target phenols in good isolated yields. Moreover, aryl chlorides were successfully employed as substrates. This methodology also provides a direct pathway for the formation of deoxyphomalone, which displayed a significant anti-proliferation effect.